2022
DOI: 10.1155/2022/5930822
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Morphological Awareness Intervention in Enhancing L2 Postgraduate Students’ Productive Vocabulary Breadth

Abstract: The significance of vocabulary knowledge in academic development and having a sufficient vocabulary in language learning cannot be overstated. Research has shown that postgraduate students studying English as a second language (L2) lack vocabulary and require improving it. This research study was conducted to investigate the role of morphological awareness and its relation to productive vocabulary breadth and explore the function of teaching L2 postgraduate students in intervention for improving their producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Morphological awareness depends on analytic and synthetic aspects. Analytic morphology focuses on breaking words into morphemes, while synthetic morphology focuses on derivations and word formation (Asaad et al,2022). Morphological awareness facilitates students' understanding and retrieving of English vocabularies that include different morphemes (Jiang & Kuo,2019).…”
Section: Review Of Literature and Related Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Morphological awareness depends on analytic and synthetic aspects. Analytic morphology focuses on breaking words into morphemes, while synthetic morphology focuses on derivations and word formation (Asaad et al,2022). Morphological awareness facilitates students' understanding and retrieving of English vocabularies that include different morphemes (Jiang & Kuo,2019).…”
Section: Review Of Literature and Related Studiesmentioning
confidence: 99%
“…Thus, it is recommended that morphology instruction be introduced to middle school students since the textbooks focus on academic language (Goodwin et al, 2017). Asaad et al (2022) investigated the effect of derivational morphology instruction on productive vocabulary breadth. Participants were 30 postgraduate students in Malaysia who received an EFL morphological awareness intervention for 11 sessions.…”
Section: Issn 1110-2721mentioning
confidence: 99%
See 2 more Smart Citations
“…Then Mu'jamiyah (lexical) knowledge also significantly influenced Arabic skills since it studied about vocabularies [18]. From these studies, Balaghah was identified as the most challenging aspect in Arabic, followed by Nahwu and Shorof [19]. Balaghah, which encompasses Arabic semantics and rhetoric, involves the understanding of the meanings of words, their usages, and the ability to express ideas eloquently and persuasively.…”
Section: Introductionmentioning
confidence: 99%